2017
DOI: 10.1007/s10554-017-1084-4
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial perfusion imaging with PET

Abstract: Noninvasive assessment of coronary artery disease remains a challenging task, with a large armamentarium of diagnostic modalities. Myocardial perfusion imaging (MPI) is widely used for this purpose whereby cardiac positron emission tomography (PET) is considered the gold standard. Next to relative radiotracer distribution, PET allows for measurement of absolute myocardial blood flow. This quantification of perfusion improves diagnostic accuracy and prognostic value. Cardiac hybrid imaging relies on the fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 77 publications
0
85
0
5
Order By: Relevance
“…3 Positron emission tomography (PET) is the non-invasive gold standard for quantitative myocardial perfusion imaging, and shows high diagnostic and prognostic utility. 4 While normal perfusion by PET largely excludes epicardial CAD and microvascular disease (MVD), it is only 46% specific for the detection of obstructive CAD. 5 Single-photon emission computed tomography (SPECT), 6,7 PET, 8,9 and cardiovascular magnetic resonance imaging (CMR) 10,11 experiments have shown that absolute quantification of the perfusion reserve is more effective at diagnosing CAD than visual assessment alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Positron emission tomography (PET) is the non-invasive gold standard for quantitative myocardial perfusion imaging, and shows high diagnostic and prognostic utility. 4 While normal perfusion by PET largely excludes epicardial CAD and microvascular disease (MVD), it is only 46% specific for the detection of obstructive CAD. 5 Single-photon emission computed tomography (SPECT), 6,7 PET, 8,9 and cardiovascular magnetic resonance imaging (CMR) 10,11 experiments have shown that absolute quantification of the perfusion reserve is more effective at diagnosing CAD than visual assessment alone.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, quantitative perfusion more accurately characterizes the extent of ischemic myocardium. 12 While PET is currently the only clinically-available technique for quantitative myocardial perfusion imaging, 4 CMR offers numerous advantages over PET. Adenosine stress CMR perfusion imaging can quantify absolute perfusion and MPR in CAD with higher spatial resolution than PET (1.5-2.5 mm versus 4-6 mm, respectively) which may improve specificity for detection of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Driessen et al [38] wrote an excellent review on the use of cardiac positron emission tomography for myocardial perfusion imaging. After a brief discussion on the principles of PET imaging, PET perfusion tracers are discussed including 82Rb which is produced by a 82Sr/82Rb generator, obviating the need for a cyclotron and therefore more convenient to implement in daily practice and the newer fluorine-labeled tracers such as 18F-flurpiridaz.…”
Section: Pet Imaging and Ffr-ct Versus Spect For The Assessment Of Comentioning
confidence: 99%
“…In July 2017 the Topical issue on Emerging concepts on Invasive and Noninvasive Coronary Physiological Assessment was published with a great overview over the various imaging modalities with a total of 15 scientific papers by the experts in this field on invasive and non-invasive flow reserve, flow-pressure relationships, microvascular dysfunction, perfusion imaging and wall shear stress [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108].…”
Section: Topical Issue On Emerging Concepts On Invasive and Noninvasimentioning
confidence: 99%
“…For the setting of non-invasive physiological assessment, Yang and Kim [11] summarize current status and future perspectives of computed tomography myocardial perfusion (CTP), focusing on technical considerations, clinical applications, and future research topics. Finally, Driessen and colleagues [12] provide a state-of-the art review of positron emission tomography (PET) imaging and its use for qualitative and quantitative assessment of myocardial perfusion. This advanced technology is by many considered the gold standard to define myocardial perfusion.…”
mentioning
confidence: 99%